Synthesis of SnO2-Fe3O4 Nanocomposites using Hydrothermal Method - Widya Twiny Rizki; Poedji Loekitowati Hariani; Addy Rachmat; Muhammad Said; Nur Hanis Hayati Hairom (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2020)
Synthesis of nanocomposite SnO2-Fe3O4 using the hydrothermal method was conducted in this study. The purpose of this study was to determine the best mass ratio in the synthesis of SnO2-Fe3O4. Nanocomposite SnO2-Fe3O4 were made with mass ratio (1:1), (1:2) and (2:1) were characterized using XRD and FTIR. The result of SnO2 characterization using XRD analysis was showed a sharp intensity peak at 2  = 26.5. The result of  Fe3O4 characterization using XRD analysis was showed a sharp intensity peak at 2  = 35.86. The XRD characterization result of SnO2-Fe3O4 (1:2) 2  = 26.74 and 34.08. Based on the XRD characterization, it can be concluded the best mass ratio for SnO2-Fe3O4 was (1:2). Characterization nanocomposite SnO2-Fe3O4 using FTIR showed the absorption band at 590 cm-1 is a characteristic peak of Sn-O and the absorption band at 563 cm-1 corresponds to Fe-O.